The Use of Self-Recording Videos as ESL Learning Method in Increasing English Learning Performance - Aprianto, Dedi; Muhlisin, Muhlisin (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
The use of Technology-based learning is currently tended to massively used in a variety of activities in schools and universities. SRV is designed to become an effective English learning method that can promote the students learning performance. This research aims at assessing or investigating the effectiveness of using SRV (Self-Recording Videos) in the university students of the Engineerings department, at the university of Bumigora. It was carried out by a quantitative research method which is descriptively statistically analyzed along with a number of samples are 14 students. This research’s sampling technique was carried out through a simple random technique, then it was accounted the sample’s number by using Slovin’s technique. The instrument of data collection used is a questionnaire consisting of 9 items, then the reliability of the instrument was tested, in which the Cronbach alpha value (0.721 > 0.60), showing that the questionnaire is reliable. The quantitative data were descriptively analyzed by using a t-test. This study suggests that the use of Self-Recording Videos (SRV) affected students’ English learning performance by assessing the average score. It is obtained that the average score is 0.8476/84.76%. In conclusion, SRV is an effective English learning method for enhancing students’ English performance.